(untitled) (Ágora de Heterodoxias, 2019)
The game theory applied to the context of cooperation between different university researchers, based on an interdisciplinary action, represents a win-win strategy, which combines the need to compete, and also to cooperate. This combination results in a change of episteme regarding our way of conceiving inter-organizational and intra-organizational relationships.